2018
DOI: 10.3892/mmr.2018.8566
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor reverts dexamethasone‑induced inhibition of prostate cancer cell proliferation and migration

Abstract: The aim of the present study was to determine the role of androgen receptor in the effect of dexamethasone on cell proliferation and migration of multiple prostate cancer cells. The prostate cancer cell lines LNCaP, 22Rv1, C4-2 and PC3 were cultured in vitro. For glucocorticoid-induced experiments, the cells were transferred and cultured in RPMI-1640 medium with 10% charcoal-stripped serum from RPMI-1640 medium with 10% fetal bovine serum for at least 24 h. The effects of dexamethasone on the proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…This compound did not affect on PTEN levels as well as the ER and PR receptors in T47D cells. Similarly, although both DU-145 and PC-3 cells express the glucocorticoid receptor (Guo et al, 2018), ASR-600 still failed to inhibit the growth of both cell lines. Recently, Sharp et al (2019) reported that while AR-V7 is rarely expressed in primary CaP, it is predominantly expressed in CRPC and frequently detected in CaP cases following ADT treatment and further increased following treatment with abiraterone or enzalutamide.…”
Section: Discussionmentioning
confidence: 97%
“…This compound did not affect on PTEN levels as well as the ER and PR receptors in T47D cells. Similarly, although both DU-145 and PC-3 cells express the glucocorticoid receptor (Guo et al, 2018), ASR-600 still failed to inhibit the growth of both cell lines. Recently, Sharp et al (2019) reported that while AR-V7 is rarely expressed in primary CaP, it is predominantly expressed in CRPC and frequently detected in CaP cases following ADT treatment and further increased following treatment with abiraterone or enzalutamide.…”
Section: Discussionmentioning
confidence: 97%
“…GRs compete with AR for DNA-binding (the GR is also negatively regulated by active AR signaling). [ 20 , 35 ] Although the 2 receptors share nearly identical DNA-binding specificities, the target genes overlap by <50% and execute unique functions in vivo. [ 20 , 35 ] Different abilities of AR and GR to interact with relatively inaccessible chromatin result in divergent binding and corresponding gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 35 ] Although the 2 receptors share nearly identical DNA-binding specificities, the target genes overlap by <50% and execute unique functions in vivo. [ 20 , 35 ] Different abilities of AR and GR to interact with relatively inaccessible chromatin result in divergent binding and corresponding gene regulation. [ 36 ] There might also be subtle differences in the DNA-binding preferences between AR and GR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different therapeutic modalities such as dexamethasone, nitric oxide, and chloroquine, which are effective in managing COVID-19, are reported to have anti-androgenic effects and suppression of TMPRSS2 ( Cronauer et al., 2007 ; Guo et al., 2018 ; Chi et al., 2020 ). Taken together, based on the current findings, testosterone is implicated in the facilitation of SARS-CoV-2 infection through upregulation of TMPRSS2 and androgen receptor (AR) activation.…”
Section: Harmful Role Of Testosterone In Covid-19mentioning
confidence: 99%